Specific Mesothelial Signature Marks the Heterogeneity of Mesenchymal Stem Cells From High-Grade Serous Ovarian Cancer. (14th October 2014) - Verardo, Roberto; Piazza, Silvano; Klaric, Enio; Ciani, Yari; Bussadori, Giulio; Marzinotto, Stefania; Mariuzzi, Laura; Cesselli, Daniela; Beltrami, Antonio P.; Mano, Miguel; Itoh, Masayoshi; Kawaji, Hideya; et al.
Abstract : Mesenchymal stem/stromal cells (MSCs) are the precursors of various cell types that compose both normal and cancer tissue microenvironments. In order to support the widely diversified parenchymal cells and tissue organization, MSCs are characterized by a large degree of heterogeneity, although available analyses of molecular and transcriptional data do not provide clear evidence. We have isolated MSCs from high-grade serous ovarian cancers (HG-SOCs) and various normal tissues (N-MSCs), demonstrated their normal genotype and analyzed their transcriptional activity with respect to the large comprehensive FANTOM5 sample dataset. Our integrative analysis conducted against the extensive panel of primary cells and tissues of the FANTOM5 project allowed us to mark the HG-SOC-MSCs CAGE-seq transcriptional heterogeneity and to identify a cell-type-specific transcriptional activity showing a significant relationship with primary mesothelial cells. Our analysis shows that MSCs isolated from different tissues are highly heterogeneous. The mesothelial-related gene signature identified in this study supports the hypothesis that HG-SOC-MSCs are bona fide representatives of the ovarian district. This finding indicates that HG-SOC-MSCs could actually derive from the coelomic mesothelium, suggesting that they might be linked to the epithelial tumor through common embryological precursors. Stem Cells 2014;32:2998–3011